2016
DOI: 10.1111/ijjs.12049
|View full text |Cite
|
Sign up to set email alerts
|

Health‐care Work in Globalization: News Reports on Care Worker Migration to Japan

Abstract: Health-care worker migration has emerged as a social issue in Japan, contrary to it has in Indonesia. This article shows how national contexts affected by globalization have shaped social understandings and policies towards healthcare worker migration in the two societies over time. Analyses of news coverage in the Japanese and Indonesian national media reveal a gap of social responses toward this change. The Japanese are more likely to respond negatively to health-care worker migration; yet they intend to fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…However, there are some advantages to employing foreign nurses. Ogawa et al [20] reported that 75% of hospitals that employed the rst batch of Indonesian nurses were satis ed or very satis ed with them, and that these nurses had a bright personality (92.9%), and an appropriate attitude towards patients (89.3%). This led hospitals to change their mindset, and encouraged Japanese staff to develop a better understanding of different cultures.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are some advantages to employing foreign nurses. Ogawa et al [20] reported that 75% of hospitals that employed the rst batch of Indonesian nurses were satis ed or very satis ed with them, and that these nurses had a bright personality (92.9%), and an appropriate attitude towards patients (89.3%). This led hospitals to change their mindset, and encouraged Japanese staff to develop a better understanding of different cultures.…”
Section: Discussionmentioning
confidence: 99%
“…Those who fail and return home are allowed to re-enter Japan on a short-term visa and re-sit the national examination. In 2015, the pass rate for the nursing exam among Indonesians was 5 percent, while 55 percent of candidates passed the caregiver test (Shinohara, 2016). Some decided to leave Japan before taking the exams; even among those few who actually passed the exam, many decided to return home (Takahata, 2016).…”
Section: Recruiting “Not-yet-so” Skilled Workersmentioning
confidence: 99%
“… 8. The number included 481 nurses and 754 care workers from Indonesia, 337 nurses and 630 care workers from the Philippines, and 21 nurses and 117 care workers from Vietnam (Shinohara, 2016: 10). …”
mentioning
confidence: 99%
“…Once accepted into the program, they receive basic language training, and start their career in Japan as care worker ‘candidates’ ( kaigo fukushishi koohosei ). After working in Japan for 3 years, they become eligible to take the national certification exam, but the exam, only offered in Japanese, has been considered a major hurdle for these foreign workers because it tends to evaluate skills and knowledge highly embedded in local language and culture (Lan, 2016, 2018; Shinohara, 2016). A growing number of studies (Hashimoto, 2018; Kusunoki, 2018; Nunoo, 2016; Otomo, 2016) have critically examined the language ideologies and policies behind the scheme of the EPA program through the analysis of government documents, media discourse, and results of questionnaires and interviews with various stakeholders.…”
Section: Introductionmentioning
confidence: 99%